Sjögren's syndrome 2 - Carteron, Nancy (Henry Stewart Talks, 2021)
Lymphoproliferative, Vasculitis, Gynecology (GYN), Congenital heart block (CHB), Neuropathy, Treatment, Immune-related adverse events of checkpoint inhibitors, Clinical development programs